The Boxers, China, and the world - Bickers, Robert A.; Tiedemann, R. G., 1941- (Rowman & Littlefield, 2007)
In 1900, China chose to take on imperialism by fighting a war with the world on the parched north China plain. This multi-disciplinary volume explores the causes behind what is now known as the Boxer war, examining its particular cruelties and its impact on China, foreign imperialism in China, and on the foreign imagination. The Boxers have often been represented as a force from China's past, resisting an enforced modernity. Here, expert contributors argue that this rebellion was instead a wholly modern resistance to globalizing power, representing new trends in modern China and in internation.